A Comparison of Tick Collection Materials and Methods in Southeastern Virginia. Issue 2 (5th October 2020) - Espada, Christina; Cummins, Hannah; Gonzales, Jon A; Notto, Leo; Gaff, Holly D
Abstract: In field studies of tick ecology, observed patterns may be biased by sampling methods. Results can vary by species, life stage, and habitat, and understanding these biases will improve comparisons of data across studies as well as assessment of human disease risk. A direct comparison of flagging versus dragging was conducted in southeastern Virginia. Transects were surveyed over a 6-wk period to identify differences in species and life stage collected, as well as differences between corduroy and denim material and inspection method for drags. Flagging collected more Ixodes affinis Neumann (Acari: Ixodidae) adults and Amblyomma americanum L. (Acari: Ixodidae) adults than dragging. Ground inspection was more efficient than tree inspection for collection of I. affinis adults, with no significant difference in inspection method for any other species or life stage. Corduroy was found to be more effective than denim in collecting nymphal A . americanum, although this may be an artifact of three large samples for corduroy collection of these ticks. There was no significant difference in Ixodes scapularis Say (Acari: Ixodidae) collection in any comparison. Dragging, tree inspection, and denim were not found to be more efficient in any scenario. This is the first comparison of flagging and dragging conducted in the southeastern United States. The community composition of ticks in this region greatly differs from regions where studies of these commonly used sampling techniques have been conducted. As the distributions of ticks continue to change over time, it will be important to evaluate best practices annually.